Botanical compounds to combat vineyards mealybugs: An ideal alternative for organic vitiviniculture - Peschiutta, María Laura (2018)
The vine mealybug (Planococcus ficus) is a major pest in vineyards and is widespread in most grape-growing areas, however, to date; few organic products have been tested to combat them. Mealybugs have an important waxy cover, which protects them from most synthetic insecticides. This class of insecticides could cause damage to the ecosystem and human health, and therefore the current need for viticulture is centered in searching novel formulations based on botanical products to fight pests in a healthier way and maintaining the sustainability of agricultural systems. In this review we show that, despite the negative impact of mealybugs against economically important crops, such as vineyards, there are few studies related to organic control using natural compounds (botanical extracts and / or essential oils). However, many of these studies are incomplete because they did not include field application or phytotoxicity tests in crops.  We discuss the extent of knowledge of botanical compounds for mealybug control and provide main research lines for the development of environmentally friendly pest control products.